STUDY OF THE MECHANICAL PROPERTIES FOR UNSATURATED POLYESTER REINFORCED BY NATURAL FIBERS - Musa, Bushra H; Nassif, Rafah A; Hadi, Enass M (Al-Nahrain Journal of Science, 2018)
Banana fiber at present is a waste product of banana cultivation. Moreover, without anyadditional cost input.This study was carried out to investigate the effect of pseudo-stem banana fibers in the wovenfabric configuration on the mechanical properties of unsaturated polyester composite. It was foundthat the addition of pseudo- stem banana woven fabric increased in the impact, compression, andflexural strength. The results showed that the impact strength on the pseudo- stem banana wovenfabric reinforced (UP) composite is increased by 22% compared to virgin (UP), while flexural andcompression strength on the composite is increased by 15% and 12% respectively.